Otimização da produção e caracterização química de um bioherbicida produzido por Mycoleptodiscus indicus - Portela, Valéria Ortaça (2021)
The research and commercial production of bioherbicides in Brazil occur to a lesser extentncompared to biopesticides and biofungicides. The aim of the study was to optimize the production of a bioherbicide by the fungus Mycoleptodiscus indicus in submerged and solid fermentation, to identify a chemical structure of chemical molecules. In order to optimize the production of metabolites in a culture medium with sugarcane bagasse substrate, Plackett-Burman and Central Rotational Composite designs were used. The optimized variables were temperature, temperature, pH, volume of water in the culture medium, concentration of glucose and yeast extract. Fungal metabolites were emitted in detached leaves of Cucumis sativus, Conyza sp. and Sorghum bicolor. Ecotoxicological testicles assess escape and acute exposure of Eisenia andrei earthworms to fungal metabolites. For chemical identification of these molecules, the fungus was cultivated in three culture media based on sugarcane bagasse (SB) or oat bran + rice (OR) or rice (RI). The extracts were obtained with 99% ethanol and derivations using acetic anhydride/pyridine and hydrochloric/methanolic acid. The chemical characterization of the volatile acetylated/methylated compounds was performed by chromatography and mass spectrometry. The bioherbicide potential of the extracts was evaluated in seeds, detached leaves and growing plants of C. sativus. The production of phytotoxic metabolites was optimized at 35 ºC, 50 rpm and 1.5 g L -1 of glucose and in continuous fermentation at intervals of 30-37ºC and 14-32 mL of water. The metabolites caused severe damage to germination, initial non-growth and leaves of the three plants. At the dose of 57 g L-1 of the bioherbicide there was a greater reduction in the biomass of E. andrei, while at the lower dose (1.78 mg L-1) there was an increase in this biomass. At the doses tested, the metabolites of M. indicus were not toxic to earthworms. Six compounds common to the three extracts SB, OR and RI were identified: methyl-latodoratin (1), palmitic acid (2), elaidic acid (3), glycerol (4), benzyl benzoate (5) and iditol (6). In extract OR and RI, linoleic acid was identified (7), while in extract SB, 4-acetyl-2-carene was detected (8). Asteric acid (9) was identified as the major component of the three extracts. The SB and OR extracts resulted in damage to detached leaves, but only SB inhibited germination. When sprayed onto leaves, the three extracts reduced plant growth. With these data it is possible to establish the following order of bioherbicidal efficiency of the obtained extracts: SB> OR> RI.